Cutaneous and Gastrointestinal Symptoms in Two Patients with Systemic Mastocytosis Successfully Treated with Omalizumab - Sofie Lieberoth; Simon Francis Thomsen (Case Reports in Medicine)
The pathogenesis of mastocytosis is not well defined and thus treatment remains challenging and remains on a palliative basis. We present two cases (a 48-year-old woman and a 57-year-old man) with indolent systemic mastocytosis in whom omalizumab (anti-IgE) reduced gastrointestinal and cutaneous symptoms significantly. This observation provides additional insight into the effects of omalizumab on systemic mastocytosis.